Network Structure in Local Wisdom-based Creative Economy Development in Baubau City, Southeast Sulawesi Province - Asmiddin, Sri Asmidar (KnE Social Sciences, 2025)
This study aims to examine the network structure in creative economic development in Baubau City, Southeast Sulawesi Province. Baubau City has a strong heritage of customs and culture, and hence a great potential in developing a creative economy based on local wisdom. However, it faces many challenges because it involves many actors, so a distribution of roles and power is needed to make the collaboration between these actors more effective. This research used a qualitative approach, and data were collected using interviews, documentation, and observation. Interviews were conducted with eight informants, namely: two people from the leadership, two creative economy actors, two academics, and two persons from the cultural community. Data were analyzed using data reduction techniques, data presentation, conclusion drawing, and verification. The results showed that the government network structure in Baubau City is hierarchical. The relationships between network structures — measured through network integration, external control, and network effectiveness — continue to point toward the dominance of unofficial power. These relationships are often based on personal or informal connections rather than formal authority. However, the lack of government presence as a management organization causes the direction of development to be less integrated and the potential of the local wisdom-based creative economy has not been utilized effectively. The ineffective role of the government has led to coordination and utilization of local potential, which have not been effectively integrated either.